Burden of congenital heart diseases in a tertiary cardiac care institute of high altitude area - Tramboo, Zubair Mushtaq; Patigaroo, Aamir Rashid; Ahmad, Nazir (International Journal of Research in Medical Sciences, 2019)
Background: Congenital heart disease is one of the major causes of mortality and morbidity in the paediatric population of both the developing and developed countries. Variability in incidence and prevalence of CHD from various countries of Indian subcontinent and rest of the world could be because of genetic, cultural, and environmental factors. The objective of the study was to find the prevalence and pattern of CHD in a tertiary care hospital in Kashmir (Jammu and Kashmir). Methods: All children admitted at territary care hospital with age 0-15 years were screened for congenital heart disease. The study was conducted for period of one year to ascertain the prevalence and spectrum of CHDs. Results: A total of 232 patients out of 23000, were found having CHDs measuring a prevalence of 10.5/1000. About 170 (73%) were the acyanotics, and 62 (27%) were cyanotic heart patients. Among the acyanotic heart diseases ventricular septal defect was the most frequent lesion seen in 54 (23%), followed by patent ductus arteriosus in 50 (22%) children. Among the cyanotic heart diseases tetralogy of Fallot was the most frequent cyanotic heart disease seen in 15 (6.4%) patients. Conclusions: Authors observed high prevalence of CHD in our population. The pattern and spectrum of CHD were comparable to national and international data.